Switching FOC Method for Vector Control of Single-Phase Induction Motor Drives - Mohammad Jannati; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz; Tole Sutikno; M. Ghanbari (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper proposes a novel vector control method based on Rotor flux Field-Oriented Control (RFOC) for single-phase Induction Motor (IM) drives. It is shown that in a rotating reference frame, the single-phase IM equations can be separated into forward and backward equations with balanced structures. In order to accommodate for these forward and backward equations, a drive system consisting of two RFOCs that are switched interchangeably, is proposed. Alternatively, these two RFOC algorithms can be simplified as a single FOC algorithm. The analysis, controller design and simulation of the proposed technique showed that it is feasible for single-phase IM drive for high performance applications.